بررسی فرایند نوستالژی در شعر خلیل الله خلیلی - Seddiqi, Zohra (Farah Research and Scientific Journal, 2025)
Nostalgia, or homesickness, is a term that has entered literature through psychology. From the perspective of psychologists, it is an emotional and motivational state, often reflecting a sense of longing caused by separation from one's homeland. Factors contributing to this feeling in poets and writers include political, social, and economic conditions, as well as poverty and migration. When examining the poetry of migrant poets, one can observe that their work is filled with nostalgic thoughts, as they strive to express their feelings, which are the result of suffering, homesickness, and the sorrow of being away from their homeland. Khalilullah Khalili, a renowned poet in the realm of contemporary Afghan poetry, who has experienced the bitter taste of migration and exile, is among these poets. In his poetry, which encompasses the depth of his thoughts, nostalgic elements are consistently observable. The purpose of this study is to examine the process of nostalgia in Khalili's poetry. The significance of this research lies in its ability to awaken a sense of patriotism in the community. The central issue in this research is the identification of nostalgic elements in Khalili's poetry, and the method used in this study is descriptive-analytical. The findings indicate that the sense and idea of nostalgia are prominently manifested in the works of Khalili, the contemporary Afghan poet. Longing, memories of youth, a sense of loneliness, hatred of internal tyranny, and foreign colonization are among the most significant factors influencing the formation of homesickness in the poetry of this patriotic poet.